Decreasing formalin concentration improves quality of DNA extracted from formalin-fixed paraffin-embedded tissue specimens without compromising tissue morphology or immunohistochemical staining. Issue 8 (9th January 2020) - Cummings, Michele; King, Henry; Hurst, James; Tanner, Georgette; Khazin, Leah; Thompson, Phillip; Gray, Allan; Gahir, Narinder; Cartlidge, Caroline; Farooq, Zara; Raveendran, Keyura; Allen, Katie; et al.
Abstract : Genomic technologies are increasingly used clinically for both diagnosis and guiding cancer therapy. However, formalin fixation can compromise DNA quality. This study aimed to optimise tissue fixation using normal colon, liver and uterus (n=8 each) by varying neutral buffered formalin (NBF) concentration (1%–5% w/v) and fixation time (24–48 hours). Fixation using 4% NBF improved DNA quality (assessed by qPCR) compared with routine (4% unbuffered formal saline-fixed) specimens (p<0.01). Further improvements were achieved by reducing NBF concentration (p<0.00001), whereas fixation time had no effect (p=0.110). No adverse effects were detected by histopathological or QuPath morphometric analysis. Immunohistochemistry for multicytokeratin and α-smooth muscle actin revealed no changes in staining specificity or intensity in any tissue other than on liver multicytokeratin staining intensity, where the effect of fixation time was more significant (p=0.0004) than NBF concentration (p=0.048). Thus, reducing NBF concentration can maximise DNA quality without compromising tissue morphology or standard histopathological analyses.